Assessment of the Microbial Quality of Five Types of Iraqi Fresh Fish in Sulaimania markets - Khidhir, Zaid Kh.; Jaff, Bahrouz M. A.; Saleh, Hatem H. (Sulaimani Journal for Pure and Applied Sciences, 2014)
The aim of this study to assess the quality of five types of local, most heavily traded and widespread in Sulaimani, fresh fish including Grass carp (Ctenopharyngodon idella), Silver carp (Hypophthalmichthys molitrix), Common carp (Cyprinus carpio), Bizz (Barbus esocinus) and Shabbout (Barbas grypus), for the period from 1st February 2010 to 1st October 2010. Analyses were achieved on a sample of twelve fishes for each type; their weight ranged 2-3Kg. different standard inspection tests were applied. Microbiology evaluation: total plate count (TPC), Psychrophilic bacterial count and Psychrotrophic counts were within the acceptable limits for all types (TPC valued 8.37 For Bizz to 25.80×105 Cfu/g for Silver carp, Psychrophils valued 6.83 for Bizz to 63.91 ×105 Cfu/g for silver carp and Psychrotrophs valued 7.7 for Bizz to 20.70×105 Cfu/g for Silver carp) but they varied in count. Wild inhabitant showed significantly better microbiology evaluation results than farmed among farmable types. Bizz and Shabbout have been sold from licensed markets had better significantly than those unlicensed markets. Pseudomonas spp. was detected in all five types in a range of 45.75 for Shabbout to 59.16 ×102 Cfu/g for silver carp with insignificant differences. Randomly selected Pseudomonas colonies revealed isolation of P.aeruginosa and P.putida.
Keywords: local fresh fish microbiology quality Sulaimani